HIGH RESOLUTION LASER SPECTROSCOPY IN COLD SUPERSONIC MOLECULAR BEAMS COOLING, REDUCTION OF DOPPLER WIDTH AND APPLICATION (Journal of Sciences, Islamic Republic of Iran)
The cooling of molecules during the adiabatic expansion of supersonic seeded molecular beams is reviewed and illustrated by the example of NO -molecules. The reduction of the Doppler width by collimation of the beam and the cooling to low rotational temperatures brings a significant simplification of the complex NO -absorption spectrum and allows its assignment. The measured rotational temperature is T = 10°K. Some examples from our work illustrate this promising technique of high resolution laser spectroscopy in cold beams